1989
DOI: 10.1016/0014-5793(89)81216-5
|View full text |Cite
|
Sign up to set email alerts
|

A stereochemical model for cytokinin activity

Abstract: The three-dimensional structures of several cytokinins were compared and a stereochemical model for cytokinin activity is proposed. This model is used to explain the difference in activity of c/s-and trans-zeatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Residues 36-47 and 148-159, which have weak electron densities, are drawn with dotted lines. rather than the N7-H form as found in the crystals of several cytokinins (see Korszun et al 1989). As expected, the cytokinin/Cdk2 co-crystals confirm the cytokinin stmcture-activity studies (for review see Skoog et al 1967, Letham 1978, Iwamura et al 1980 in that the N7, N3, and N9 of the purine must remain free of substitution because of the hydrogen bonds formed by these nitrogen atoms.…”
Section: -Alkyl-ba Derivativessupporting
confidence: 72%
“…Residues 36-47 and 148-159, which have weak electron densities, are drawn with dotted lines. rather than the N7-H form as found in the crystals of several cytokinins (see Korszun et al 1989). As expected, the cytokinin/Cdk2 co-crystals confirm the cytokinin stmcture-activity studies (for review see Skoog et al 1967, Letham 1978, Iwamura et al 1980 in that the N7, N3, and N9 of the purine must remain free of substitution because of the hydrogen bonds formed by these nitrogen atoms.…”
Section: -Alkyl-ba Derivativessupporting
confidence: 72%
“…Those study showed the dihedral angle between adenine and furfuryl residues plane to be 76-79 • [26][27][28][29][30].…”
Section: Synthesis and Structure Of Kinetinmentioning
confidence: 99%
“…CK were extracted from whole pods (fer- Figure 1. The stereochemical conformation of (trans)Z and (cis)Z (adapted from Korszun et al, 1989). Open oval, C; gray oval, N; checkered oval, O; black oval, H. tilized ovaries, 1 DAPS, 30-50 mg dry weight), embryo with cotyledons, endospermic fluid and seed coat (14 DAPS; 4-84 mg dry weight), and cotyledons (30, 40, and 50 DAPS; 16-85 mg dry weight for GC-MS-SIM and 500-900 mg dry weight for full-scan GC-MS).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The cis-isomer occurs when the hydroxyl group of the isopentenyl side chain is oriented toward the N-1 position of the purine ring, whereas in the trans-isomer the hydroxyl group is oriented away from the purine ring (Korszun et al, 1989;Fig. 1).…”
mentioning
confidence: 99%